Strategic Role of Human Resource Management in Organizations in the Republic of Macedonia - Eftimov, LJupcho; KJosev, Sasho; Trpeski, Predrag (Faculty of Business and Management Sciences, Novo mesto & Faculty of Business, Management and Informatics, Novo mesto, 2016)
Today, strategic management and human resource management are the two most important interests and tasks of modern management. Their mutual integration is a prerequisite for achieving organizational competitive advantage. Only when the human resource management department is involved in the strategy formulation and implementation, it comes to the strategic management of human resources. Although a great number of chief executive officers expresses high awareness of the importance of involving human resource management in the process of strategic execution, for which it is traditionally in charge, as well as in the process of the strategic planning, there is no mutual agreement on the extent to which it should be involved in the process. Numerous studies that have been conducted all over the world suggest different results, with different success in achieving competitive advantage which is rare, valuable and difficult to imitate, however, needed for long-term survival and development of the organizations. In order to determine the (strategic) role of human resource management in organizations in Republic of Macedonia and to make a comparison with the situation in the developed countries, a survey of 67 organizations was conducted, and in the paper, the results of the survey are analyzed in details.
Keywords: organizational strategy, strategic human resource management, competitive advantage, Macedonia